2005
DOI: 10.1213/01.ane.0000153862.95153.2e
|View full text |Cite
|
Sign up to set email alerts
|

Caudal Additives in Pediatrics: A Comparison Among Midazolam, Ketamine, and Neostigmine Coadministered with Bupivacaine

Abstract: Single-shot "kiddie caudal" with bupivacaine alone is losing popularity because of its duration of 4-8 h. In a prospective randomized double-blind clinical study, we assessed and compared the efficacy of ketamine, midazolam, and neostigmine coadministered with bupivacaine in a caudal epidural to provide intraoperative and postoperative pain relief. Eighty children (ASA status I) aged 5-10 yr undergoing unilateral inguinal herniotomy were allocated randomly in equal numbers (n = 20) into 4 groups to receive a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 24 publications
6
71
0
Order By: Relevance
“…Adjunct clonidine in the dose range of 1-2 mg/kg doubles the duration of analgesia compared with plain local anesthetics. 4 Dexmedetomidine (DEX) is a highly selective a 2 agonist with sedative and analgesic properties. It has an a 2 /a 1 selectivity ratio of 1600 : 1, which is eight times more potent than clonidine (200 : 1).…”
mentioning
confidence: 99%
“…Adjunct clonidine in the dose range of 1-2 mg/kg doubles the duration of analgesia compared with plain local anesthetics. 4 Dexmedetomidine (DEX) is a highly selective a 2 agonist with sedative and analgesic properties. It has an a 2 /a 1 selectivity ratio of 1600 : 1, which is eight times more potent than clonidine (200 : 1).…”
mentioning
confidence: 99%
“…AK Pan 20,22 et al found no significant changes in the mean respiratory rate and oxygen saturation in all the groups.…”
Section: The Following Studies Are Consistent With Our Studymentioning
confidence: 86%
“…[6][7][8] Levobupivacaine and racemic bupivacaine show equally effective potencies for spinal anaesthesia with regard to time of onset, duration of motor and sensory block, and haemodynamic changes produced after any form of bupivacaine. Intrathecal levobupivacaine in general is a safer and more reliable local anaesthetic for lower limb surgeries.…”
Section: Discussionmentioning
confidence: 99%